Pediatric Dysfunctional Breathing: Proposed Components, Mechanisms, Diagnosis, and Management - Barker, Nicki; Thevasagayam, Ravi; Ugonna, Kelechi; Kirkby, Jane (Frontiers in Pediatrics, 2020)
Dysfunctional breathing (DB) is an overarching term describing deviations in the normal biomechanical patterns of breathing. It occurs in both children and adults and has a significant impact on quality of life, performance and functioning. DB has two components; breathing pattern disorders (BPD) and inducible laryngeal obstruction (ILO) which are intricately related and often co-exist. The most common symptoms of DB are shortness of breath and chest discomfort, often during exercise, leading to DB being misdiagnosed as asthma. The picture is further complicated by the common co-presentation of DB and asthma. DB is diagnosed through expert history taking and a choice of appropriate tests/examinations which may include spirometry, breathing pattern analysis, exercise testing and exercise testing with laryngoscopic examination. Use of the algorithm presented will aid decision making regarding choosing the most appropriate tests and understanding the diagnostic implications of these tests. Questionnaire-based tools are useful both for assessment purposes and as outcome measures for the efficacy of treatment when applied pre and post intervention. These may be targeted at diagnosis, monitoring of symptoms or at measuring quality of life. Patients with DB typically present with normal spirometry and an altered breathing pattern at rest which is amplified during exercise. In cases of ILO, abnormalities of the upper airway such as cobblestoning are commonly seen followed by abnormal activity of the upper airway structures provoked by exercise. This may be associated with a varying degree of stridor. Associated conditions such as asthma, extra-oesophageal reflux and rhinitis must be treated appropriately and well controlled before any directed therapy for DB can be started if therapy is to be successful. DB is commonly treated with a course of non-pharmaceutical therapy. The therapy is provided by an experienced physiotherapist, speech and language therapist or psychologist depending on the dominant features of the DB presentation and some patients will benefit from input from more than one of these disciplines. An individualised treatment program based on expert assessment and personalised goals will result in a return to normal function with reoccurrence being rare.